Genome-wide identification of conserved regulatory function in diverged sequences - Taher, Leila (Cold Spring Harbor Laboratory Press, 2011)
Plasticity of gene regulatory encryption can permit DNA sequence divergence without loss of function. Functional information is preserved through conservation of the composition of transcription factor binding sites (TFBS) in a regulatory element. We have developed a method that can accurately identify pairs of functional noncoding orthologs at evolutionarily diverged loci by searching for conserved TFBS arrangements. With an estimated 5% false-positive rate (FPR) in approximately 3000 human and zebrafish syntenic loci, we detected approximately 300 pairs of diverged elements that are likely to share common ancestry and have similar regulatory activity. By analyzing a pool of experimentally validated human enhancers, we demonstrated that 7/8 (88%) of their predicted functional orthologs retained in vivo regulatory control. Moreover, in 5/7 (71%) of assayed enhancer pairs, we observed concordant expression patterns. We argue that TFBS composition is often necessary to retain and sufficient to predict regulatory function in the absence of overt sequence conservation, revealing an entire class of functionally conserved, evolutionarily diverged regulatory elements that we term “covert.”